Relation of Gut Microbes and L-Thyroxine Through Altered Thyroxine Metabolism in Subclinical Hypothyroidism Subjects - Yao, Zhenyu; Zhao, Meng; Gong, Ying; Chen, Wenbin; Wang, Qian; Fu, Yilin; Guo, Tian; Zhao, Jiajun; Gao, Ling; Bo, Tao (Frontiers in Cellular and Infection Microbiology, 2020)
Thyroxine metabolism is an important topic of pathogenesis research and treatment schedule of subclinical hypothyroidism (SCH). L-Thyroxine replacement therapy (LRT) is usually recommended for severe SCH patients only. Our previous studies reported that disordered serum lipid of mild SCH people could also benefit from LRT. However, the benefits were different among individuals, as shown by the variations in drug dosage that required to maintain thyroid-stimulating hormone (TSH) stability. Alternative pathways, such as sulfation and glucuronidation of iodothyronine, may play a role in thyroid hormones metabolism in peripheral tissues aside from thyroid. Conjugated thyroxine can be hydrolyzed and reused in tissues including gastrointestinal tract, in which gut microbiota are one of the most attractive physiological components. On this site, the roles of gut microbiota in thyroidal metabolism should be valued. In this study, a cross-sectional study was performed by analyzing 16S rDNA of gut microbiota in mild SCH patients treated with L-thyroxine or not. Subjects were divided by serum lipid level, L-thyroxine treatment, or L-thyroxine dosage, respectively. Relationship between gut microbiome and serum profile, L-thyroxine treatment, and dose were discussed. Other metabolic disorders such as type 2 diabetes and hypertension were also taken into consideration. It turned out that microbiome varied among individuals divided by dose and the increment of L-thyroxine but not by serum lipid profile. Relative abundance of certain species that were associated with thyroxine metabolism were found varied among different L-thyroxine doses although in relatively low abundance. Moreover, serum cholesterol may perform relevance effects with L-thyroxine in shaping microbiome. Our findings suggested that the differences in L-thyroxine dosage required to maintain TSH level stability, as well as the SCH development, which was displayed by the increased L-thyroxine doses in subsequent follow-up, had relationship with gut microbial composition. The reason may due to the differences in thyroxine metabolic capacity in gut. In addition, the metabolic similarity of iodothyronines and bile acid in gut also provides possibilities for the correlation between host's thyroxine and cholesterol levels. This study was registered with ClinicalTrials.gov as number NCT01848171.